Assessment of Postoperative Nurses’ Interventions for the Patients with Laparoscopic Cholecystectomy at Baghdad Teaching Hospitals - Kadhim, alaa; Kadhim, Haleema (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The study aimed to assess the postoperative nurses’ intervention for the patients with laparoscopic cholecystectomy and to determine the relationship between Nurses’ interventions and their demographic characteristics. Methodology: Quantitative design (a descriptive study) was started from 20th November 2012 up to 1st September 2013. Non-probability (purposive sample) of (50) nurses, who were working in surgical wards, were selected from Baghdad teaching hospitals (Baghdad Teaching Hospital, Digestives System and Liver Teaching Hospital, AL-Kindy Teaching Hospital, and AL-Kadhimiyia Teaching Hospita). The data were collected through the use of a constructed questionnaire, which consisted of two parts; the first part includes the page of demographic data which contains (10) items and the second part which includes (5) domains in (46) subdomain of postoperative nurses’ interventions for the patients with laparoscopic cholecystectomy, through direct observant approach by the mean of the designed interventions checklist, Reliability of the questionnaire was determined through a pilot study and the validity through a panel of (12) experts. Descriptive statistical analysis procedures (frequency, percentage, mean of score, Standard Deviation and Relative Sufficiency), and inferential statistical analysis procedures (Reliability Coefficient, contingency coefficient and chi- square test) were used for the data analysis under application of the statistical package of social science (SPSS) ver. (10.0). Results: The findings of the study indicated that there is a weak assessment of postoperative nurses’ interventions for the patients with laparoscopic cholecystectomy at Baghdad teaching hospitals, and the findings indicated that the most of study items responding of questionnaire were (84.78%) significant differences. There was no significant relationship between nurses’ gender, age, years of experience and their assessment, while there was significant relationship between the level of education, sharing in training sessions which established (by the hospital, by other hospitals, or by other institutions), duration of the training session, Number of training sessions and assessment of postoperative nurses’ interventions Recommendations: The study recommended that special training session, concerning all nurses’ surgical wards for postoperative nursing interventions (Laparoscopic Cholecystectomy Patient) at inside or outside Iraq, and booklets should be designated and presented to all nurses’ surgical wards, in addition to increasing the number of professional nurses’ graduate from the colleges of nursing to the enrolled in surgical wards.